Validation of a multiplexed immunoassay for immunological analysis of pre erythrocytic malaria vaccines - L. K. Stockdale; S. Provstgaard-Morys; D. Bellamy; D. Woods; K. Rapi; A. Bajer; B. Hollingdale; O. Muñoz; S. Malik; A. V. S. Hill; K. J. Ewer (npj Vaccines)
Abstract The primary immunological readout for clinical trials of R21/MatrixM™ malaria vaccine, is total IgG antibody specific to the central four amino acid NANP repeat region of the circumsporozoite protein. A multiplexed assay, which includes NANP, was developed and validated for four antigens representing components of the R21 immunogen. Initial assay optimisation included validation of the HBsAg international standard. Further validation performed in Oxford covered intra and inter-assay, and inter-operator variability, accuracy of QC and standard curve material, and included bridging to a singleplex NANP6 ELISA. The assay was shown to be robust and specific, with a broad dynamic range. We report a strong linear relationship between NANP6 IgG as measured by the singleplex ELISA and the multiplexed assay with rho values of 0.89 and 0.88 for two separate clinical trials (both p < 0.0005). This assay can be used to measure antibodies specific to the CSP NANP repeat region, CSP C-term region, full length R21 and HBsAg.